KAJIAN LITERATUR INTEGRASI KONSEP GREEN CHEMISTRY DALAM PEMBELAJARAN KIMIA - Erdiana Gultom (Universitas Samudra, 2026)
The industrial revolution and technological advances have had a significant impact on human life, but they have also created serious environmental problems due to the use of hazardous chemicals. The purpose of this study is to examine the role of education, particularly chemistry education, in creating more environmentally friendly chemical processes. The application of green chemistry principles depends not only on industry but also on the world of education, particularly science and chemistry learning. Therefore, it is important to revitalize science/chemistry learning to orient it towards the principles of green chemistry. Thus, chemistry education can contribute significantly to shaping a generation that thinks critically, innovatively, and has an environmental perspective. This research method uses a narrative literature review. The results of the literature review indicate that the topic of sustainability and education has experienced rapid development to date. The results of the analysis reflect the increasing global attention to sustainable education. Through a project-based learning approach and the support of educational policies that support sustainability, education can become a strategic instrument to build a generation that cares about the environment and is able to face global sustainability challenges scientifically and ethically. Based on the results of the analysis of ten journals, it is seen that the revitalization of chemistry learning can be done through various innovative strategies: Active learning approaches (PjBL, PBL, STEAM) that encourage students to solve real problems on environmental issues, Utilization of digital technology and virtual laboratories that support safe, efficient, and waste-free learning, and Reorientation of the curriculum and strengthening of sustainability values ​​so that chemistry education contributes to the Sustainable Development Goals (SDGs). Keywords: chemistry learning, green chemistry, revitalization, science education, Sustainable Development Goals